DESIGN VISUALISASI LOGO SEBAGAI IDENTITY PROGRAMS DI DIVISI RAHARJA ENRICHMENT CENTRE - Anita B Wandanaya; Dewi Immaniar; Maryana Astuti (Universitas Raharja, 2014)
One of the important things in a visual media institution is a public institution of the logo identity. Identity logo itself has a meaning as an identity that represents the image of an institution. Division Raharja Enrichment Centre was commissioned to complete the implementation of Tri Dharma on Higher Education Prog which concentrates on research and service to society. Enrichment programs Prog Centre issued has not had a logo identity. Without the identity logo to the program have not been able to realize the identity of ownership to the public. For that, it takes a logo identity for each of the programs Raharja Enrichment Centre which can be interesting and can be implemented as the identity of the visual. The one of methode in this study used Design Analys Method with applications supporting Adobe Illustrator CS5 applications such as processor design objects vector image, while Adobe Photoshop CS5 application used to process bitmap images and Design Concept Plan contains the media. With the logo identity of each of these programs, the public will be easily understood by looking at a consistent look and is easily recognizable because it has special characteristics in each of its programs. From the design of the logo identity is expected for subsequent years may give a different look and appeal in introducing programs of the Raharja Enrichment Centre.